Integrated Planning and Control for Collision Avoidance Systems - Yi, Boliang (Schriftenreihe / Institut für Mess- und Regelungstechnik, Karlsruher Institut für Technologie, 2018)
Collision avoidance systems like emergency braking assist systems have demonstrated their effectiveness in increasing the safety of vehicle passengers in various studies. To further increase the effectiveness of collision avoidance systems, the exploitation of the lateral free space by evasive maneuvers is being investigated in this book. This work focuses on methods for integrated trajectory planning and vehicle dynamics control in collision avoidance scenarios by combined evasion and braking.